2014
DOI: 10.4132/koreanjpathol.2014.48.3.241
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Metastatic Angiosarcoma Diagnosed by Liquid-Based Preparation: Peculiar Cytoplasmic Changes

Abstract: Angiosarcoma with predominantly epithelioid features is a rare soft tissue neoplasm and the interpretation of its cytopathologic findings may be difficult. We report a case of metastatic angiosarcoma with predominantly epithelioid features diagnosed by liquid-based cytology. The cytopathologic findings in this case differed from those of the conventional preparation and we found a clean background, no hyperchromatic nuclei and several cytoplasmic changes, including intracytoplasmic vacuoles with peculiar shape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Cell-block ICC is considered useful for diagnosing malignant pleural effusion, especially for patients in whom a conventional cytology examination does not result in a definitive diagnosis ( 15 ), and is widely used in clinics for patients suspected of having mesothelioma or lung cancer. One report previously showed the utility of cell-block ICC to diagnose the malignant pleural effusion caused by angiosarcoma ( 16 ), and other reports showed that ICC with fine-needle aspiration specimens resulted in a definitive diagnosis of angiosarcoma ( 17 - 19 ). In the present case, we retrospectively performed cell-block ICC and obtained consistent results ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Cell-block ICC is considered useful for diagnosing malignant pleural effusion, especially for patients in whom a conventional cytology examination does not result in a definitive diagnosis ( 15 ), and is widely used in clinics for patients suspected of having mesothelioma or lung cancer. One report previously showed the utility of cell-block ICC to diagnose the malignant pleural effusion caused by angiosarcoma ( 16 ), and other reports showed that ICC with fine-needle aspiration specimens resulted in a definitive diagnosis of angiosarcoma ( 17 - 19 ). In the present case, we retrospectively performed cell-block ICC and obtained consistent results ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…They considered these features to be important diagnostic clues for angiosarcoma [ 10 ]. In contrast to conventional preparation, Jung and Kim reported a metastatic angiosarcoma diagnosed from liquid-based cytology [ 11 ]. The following cytological features different from conventional preparation were emphasized: a clean background, absence of hyperchromatic nuclei, intracytoplasmic vacuoles with peculiar shapes, juxtanuclear condensation, and perinuclear clearing [ 11 ].…”
mentioning
confidence: 99%
“…In contrast to conventional preparation, Jung and Kim reported a metastatic angiosarcoma diagnosed from liquid-based cytology [ 11 ]. The following cytological features different from conventional preparation were emphasized: a clean background, absence of hyperchromatic nuclei, intracytoplasmic vacuoles with peculiar shapes, juxtanuclear condensation, and perinuclear clearing [ 11 ]. Similarly, in our case, the LBC preparation with SurePath made it easier to identify hemophagocytosis, endothelial wrapping, and cytoplasmic lumina/vacuoles without the bloody background in conventional preparation.…”
mentioning
confidence: 99%